Motives for Women’s Participation in Military Conflicts: The Ukrainian Case - Lapėnaitė, Miglė (Politologija, 2022)
This article analyzes the motives for direct (in military actions) and non-direct (in administrative or military support actions) participation of Ukrainian women in the ongoing Russian-Ukrainian military conflict that began in 2014. It aims to reveal the motives that have led pro-Ukrainian women to take part in defending their country by allowing the participants of the study to speak for themselves. The article draws on twenty (20) e-interviews with women who were involved in the war in Ukraine and five (5) semi-structured interviews with people who due to their professional activities were able to observe the conflict from the inside (journalists, NGO workers, and war photographers), as well as secondary sources available. Content analysis of the interview data was implemented. The article identifies four main motives for participation in war: patriotism, grievances, personal loss and suffering, and women’s empowerment. This information corresponds with similar studies conducted elsewhere in the region.